PENYULUHAN PROGRAM PENGUATAN OTOT EKSTREMITAS BAWAH PADA BURUH PABRIK BATIK NUR HASIDA - Arif Pristianto; Adinda Dela Nastiti; Muhammad Faris Fatahillah; Irvan Prasetya; Aulia Rahman; Salma Hira Ayu Setyara (Jurnal Pengabdian Ilmu Kesehatan, 2022)
Batik is one of the works and cultural heritage of Indonesia which is a combination of art and technology by the ancestors of the Indonesian nation. Batik has various types and various ways of making such as written, stamped, dyed, and many more. With so many existing batik-making processes, the scope of human movement is certainly very broad. This can cause various complaints, especially in the lower extremity body because the position of the body when working is not in an ergonomic position. In this case, of course, the role of physiotherapy is needed to provide direction and solutions to complaints that occur. This is what happened to the batik craftsmen of Nur Hasida who felt a complaint in the form of achy pain in the lower extremities of the body. Therefore, several exercises were carried out such as warming-up (sprinting in place and jumping jacks), strengthening (squats, split squats, side leg raises and reverse lunges), and stretching (quad stretches, inner thigh stretches, and toe extensions). to strengthen the muscles of the lower extremities as well as education about ergonomic positions while working.